2004
DOI: 10.1128/jb.186.13.4276-4284.2004
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression and Purification of Active Divercin V41, a Class IIa Bacteriocin Encoded by a Synthetic Gene in Escherichia coli

Abstract: Divercin V41, a class IIa bacteriocin with strong antilisterial activity, is produced by Carnobacterium divergens V41. To express a recombinant version of divercin V41, we constructed a synthetic gene that encodes the mature divercin V41 peptide and then overexpressed the gene in pET-32b by using the T7 RNA polymerase promoter in the Escherichia coli Origami (DE3)(pLysS) strain. The DvnRV41 peptide was expressed as a translational fusion protein with thioredoxin and accumulated in the cell cytoplasm in a solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 67 publications
0
58
0
Order By: Relevance
“…In this particular case of extensively modified thurincin H, the sulfur-to-␣-carbon bonds were very unique and to date are reported to exist in only three other bacterial peptides (24)(25)(26). These bonds are not reported in proteins expressed by commonly used expression hosts, such as E. coli (27) or lactic acid bacteria (11), rendering the deletion mutant a logical host for expression of site-directed mutants. The pGW131 complementation experiments indicated that the thurincin H prepeptide translated from the plasmids was correctly modified by the chromosomally encoded radical SAM enzyme, processed, and exported to the extracellular environment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this particular case of extensively modified thurincin H, the sulfur-to-␣-carbon bonds were very unique and to date are reported to exist in only three other bacterial peptides (24)(25)(26). These bonds are not reported in proteins expressed by commonly used expression hosts, such as E. coli (27) or lactic acid bacteria (11), rendering the deletion mutant a logical host for expression of site-directed mutants. The pGW131 complementation experiments indicated that the thurincin H prepeptide translated from the plasmids was correctly modified by the chromosomally encoded radical SAM enzyme, processed, and exported to the extracellular environment.…”
Section: Discussionmentioning
confidence: 97%
“…In homologous expression of less extensively modified bacteriocins, only the mature bacteriocin-encoding sequence was incorporated into the expression vector (9,27). However, the leader peptide of the thurincin H precursor was included in our con- structs, since the leader peptide of the bacteriocins can play essential roles in the formation of lanthionine/methyllanthionine in lantibiotics, as well as keep the bacteriocin prepeptide in an inactive state and facilitate exportation (31).…”
Section: Discussionmentioning
confidence: 99%
“…As the roles of the disulfide bonds, of the consensus sequence YGNGVXCX 4 C, and of the positively charged residues mainly located in the N-terminal domain have been studied previously, here we designed variants with single amino acid replacements located in the central and C-terminal parts of the molecule, using a genetic approach which previously has been proven to be efficient (47). We also took advantage of our knowledge of the production of DvnRV41, a recombinant form of this two-disulfide-bond class IIa bacteriocin which retained the antibacterial activity of the natural bacteriocin (44,60), in order to develop an efficient production system for the desired variants. In order to determine the precise role of the amino acid side chains, each selected amino acid was replaced by another amino acid belonging to a similar polarity group, in agreement with the amino acid Venn diagram (51).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting system allowing large-scale production of pure recombinant piscicolin 126 at 26 mg/liter from a native DNA was reported with E. coli AD494(DE3) (72). Divercin V41 and piscicolin 126 have been expressed as bacteriocinthioredoxin chimeric soluble proteins requiring, respectively, enzymatic or chemical treatment to release the recombinant bacteriocin (72,155). Importantly, both systems provide ease of purification and a high yield of bacteriocins with correct disulfide bond formation.…”
Section: Purification and Heterologous Production Of Class Iia Bactermentioning
confidence: 99%